Belle of the brawl - Harrison, Lisi (Harrison, Lisi. Alphas., 2010)
Skye Hamilton, Charlie Deery, and Allie A. Abbott are enrolled in the exclusive Alpha Academy, where the best dancers, writers, musicians, and inventors face eliminations until there is only one left standing.